Evaluation of pharmacotherapy used on geriatric population in an institution of special regime with the screening tool of older persons’ potentially inappropriate prescriptions (STOPP) criteria - HERRERA E., Ana María; LÓPEZ, José Julian (Vitae, 2016)
Background: Geriatric patients represent a major challenge for appropriate prescription because they have significant changes in vital areas, multiple comorbidities among other things that encourage their fragility. In light of current evidence, the number of prescription errors increases with age and with the number of drugs USED, showing that people over 65 is at greater risk of medical error when more than 8 drugs are consumed. Objectives: To identify and describe the inappropriate medicines in elderly people in order to propose an institutional prescription guide based on the results of the application of the Screening Tool of Older Persons’ Potentially Inappropriate Prescriptions (STOPP) assessment methodology. Methods: A cross-section observational study with a retrospective collection of information was carried out in order to identify the frequency of inappropriate prescriptions in 300 elderly patients that were over 65 years, with a consumption of more than 5 medications and applying the STOPP criteria. The study was made in a special regime medical institution, reviewing medical records and considering variables such as number of medications, indications, dosage, therapeutic duplication, interactions and contraindications, among others. Results: The principal diagnosis was hipertension (47%) followed by diabetes mellitus (10%) and other hypothyroidisms (4%).After applying the STOPP criteria to each of the medical records, it was found that 50.7% (152) of the studied population had at least one inappropriate prescription distributed as follows: 2 prescriptions had 4 STOPP criteria, 7 prescriptions had 3 STOPP criteria, 28 had 2 STOPP criteria and 115 had 1 STOPP criteria. Conclusions: It was found that half of the prescriptions have at least one inadequate prescribed criteria, being the most important the inappropriate use of not indicated drugs or without an indication. Finally, guidelines for the rational use of drugs in the elderly with every detail of this institution are proposed.